VASTOS CÂNONES E PENSAMENTOS PÓS-MODERNOS - Cunha, João Manuel (Organon, 2012)
The Brazilian contemporaneous writers who had chosen the cinematographiclanguage as second nature of the literary work finish by canonize the modernisttexts. Stating their predecessors, today’s fictionists affirm the hope that thatvanguard had in the democratization, amplification and education of the reader.